Immersion of virtual reality for rehabilitation - Review. (May 2018) - Rose, Tyler; Nam, Chang S.; Chen, Karen B.
Abstract: Virtual reality (VR) shows promise in the application of healthcare and because it presents patients an immersive, often entertaining, approach to accomplish the goal of improvement in performance. Eighteen studies were reviewed to understand human performance and health outcomes after utilizing VR rehabilitation systems. We aimed to understand: (1) the influence of immersion in VR performance and health outcomes; (2) the relationship between enjoyment and potential patient adherence to VR rehabilitation routine; and (3) the influence of haptic feedback on performance in VR. Performance measures including postural stability, navigation task performance, and joint mobility showed varying relations to immersion. Limited data did not allow a solid conclusion between enjoyment and adherence, but patient enjoyment and willingness to participate were reported in care plans that incorporates VR. Finally, different haptic devices such as gloves and controllers provided both strengths and weakness in areas such movement velocity, movement accuracy, and path efficiency. Highlights: No distinct relationship between immersion and improvement in motor recovery. No comprehensive agreement in enjoyment and user adherence in VR rehabilitation. Different haptic devices influenced user performance, thus. Important to consider the type of haptic devices employed in VR rehabilitation.